(untitled) (Journal of Nursing Education in Psychiatric and Mental Wellbeing, 2026)
Mental health is a fundamental component of overall well-being and plays a crucial role in an individual’s development across all stages of life. It supports the growth of cognitive, emotional, and psychomotor abilities, enabling individuals to function effectively in daily life. People with positive mental health tend to experience greater life satisfaction, demonstrate creative thinking, and show enthusiasm for learning and achieving their goals. In recent years, students at secondary and college levels have been increasingly exposed to mental health challenges arising from academic pressure, social expectations, and personal difficulties. Such challenges may negatively influence their academic performance and, in severe cases, may contribute to emotional distress and self-harm tendencies. Therefore, promoting mental well-being among students at secondary, higher secondary, and college levels has become a shared responsibility of educators, parents, school authorities, and policymakers. Adolescence is a critical and transitional period marked by rapid physical, emotional, psychological, and social changes. This stage significantly contributes to the formation of personality and overall development. Ensuring sound mental health during adolescence is essential for achieving balanced development in all aspects of life. Furthermore, mental health should be understood in connection with key psychological factors such as emotional intelligence and personality traits, as these aspects are interrelated and mutually influential. Emotional balance and well-developed personality characteristics are often associated with better mental health outcomes. Building on these relationships, this research explores how emotional intelligence and personality traits shape the mental health outcomes of high school students. Keywords-